Development and research of a digital control system for juice consumption after the diffusion apparatus in sugar production. Issue 1 (1st July 2022) - Alekseev, M V; Kudryashov, V S; Gavrilov, A N; Ivanov, A V; Kozenko, I A; Sukhanova, N V
Abstract: The article is devoted to solving the problem of stabilizing the flow rate of diffusion juice at the outlet from the buffer tank under conditions of an unstable hydrodynamic mode of operation of the diffusion apparatus in sugar production. The existing system does not provide effective stabilization of the juice consumption in case of significant fluctuations in the level and situations arise when the buffer tank is empty or overflowed. A digital control system is proposed that improves the dynamic accuracy of juice flow stabilization due to digital correction according to the integral law of setting the flow regulator according to filtered (smoothed) level values and including proportional, differential components in the correction algorithm when the level leaves the "smooth" control area. The effectiveness of the digital control system is confirmed by mathematical modeling in various modes.